„Piękniej niż w bajce”. Obóz pionierski w Arteku w polskim reportażu lat 30–50. XX wieku - Żejmo, Bożena (Acta Polono-Ruthenica, 2018)
The objective of the article is to analyze the image of the pioneer camp Artek in the Polish reportage of the 1930s–50s in the XX century. At the beginning of the 1930s, only one account about Artek, by Michał Suryc, appeared on the Polish publishing market. From the second half of the 1940s, when the communist Polish authorities began intense Stalinization, the press was enthusiastically reporting the next batch of Polish children spending wonderful and unforgettable moments in the Crimea. The most idealized picture of Artek was created by Marian Brandys in his book Journey to Artek (1953), an ideologized communist fairy-tale.